2015
DOI: 10.1007/s11427-015-4853-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of epigenetics in diabetic retinopathy

Abstract: Diabetes has become the epidemic of the 21st century, and with over 90% patients with diabetes becoming at a risk of developing retinopathy, diabetic retinopathy has emerged as a major public health concern. In spite of cutting edge research in the field, how retina and its vasculature are damaged by the diabetic milieu remains ambiguous. The environmental factors, life style or disease process can also bring in modifications in the DNA, and these epigenetic modifications either silence or activate a gene with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 89 publications
(72 reference statements)
0
19
0
Order By: Relevance
“…Several lines of studies have shown that miRNAs play a key role in diabetes and its complications, modulating multiple signaling pathways associated with DR [23][24][25]. Previous studies have shown that miR-200b and miR-146a play an essential role in diabetic retinopathy through modulation of VEGF and fibronectin [15,26].…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of studies have shown that miRNAs play a key role in diabetes and its complications, modulating multiple signaling pathways associated with DR [23][24][25]. Previous studies have shown that miR-200b and miR-146a play an essential role in diabetic retinopathy through modulation of VEGF and fibronectin [15,26].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, proinflammatory lipids, 13 epigenetic and epigenomic modifications, 14 insulin dysregulation, 15 and b-cellulin signaling, 16 which initiate and contribute to DR pathogenesis independently from hyperglycemic condition, have been identified. biochemical pathways and inflammation in diabetic retinopathy (DR) pathogenesis.…”
Section: Mechanisms Implicated In the Pathogenesis Of Drmentioning
confidence: 99%
“…Changes of tear AMP levels are likely not the cause but rather the consequence of diabetic retinopathy progression, hence, it can be used to develop bedside test for screening purposes. Currently, photographic methods and retinal image analysis to track neovascularization and increased vascular permeability in the retina can be used for screening [189][190][191], this, however, requires proper instruments, software, and well-trained human graders, making diagnosis available only in big screening centers. In order to make the screening widely accessible, easy-to-implement tests; which can be used by general practitioners, are needed.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%